The Influence of Socio-Cultural Environment and Behavior on The Incidence of Malaria in The Village of Kori Ntt (Public Health Perspective Journal, 2018)
The problems studied in this research are derived from observations and preliminary data from the SBD Health Department which shows that malaria disease is still the top ten diseases to be prioritized with morbidity rate in 2016 amounted to 4,354 souls. an increase of malaria morbidity rate occurs in 2017 amounted to 8,954 souls. The purpose of this study is to analyze the factors causing the incidence of malaria in the community residing in Kori Village. This is correlation analytical research with cross sectional approach. Â The number of sample is 280 respondents. The instruments used are questionnaires, observation sheets and checklists. Data analysis is conducted by means of multiple linear regression. The result of the research indicates (1) There is influence of socio-cultural environment on the incidence of malaria with p-value of 0,001 Î± (0,05). (2) There is influence of behavior on the incidence of malaria with p-value of 0,002 Î± (0,05). The Community should implement a healthy lifestyle, while the Department of health and local government should conduct a comprehensive health education.Â